Teaching English As Second Language through Drama for Effective Communication Skills: A Pragmatic Perspective - Idogho, Joseph Agofure (Journal of English Language Teaching and Linguistics, 2018)
Literatures have reveal that teaching English Language in a conventional classroom with all the available methodology hardly gives the students opportunity to use the language effectively or gain the competence and confidence of using the language in and outside the classroom and probably develop fluency in it: especially when English is a second language other than the learner’s language like the Nigeria situation. This paper thus opines that with the use of drama as a tool or technique in teaching English Language as second language; learners would be equipped with the essential skills of communication and gain fluency in the language. This paper therefore explores the array of models through which language exploration through drama is related to Language Acquisition theories. The paper examines the theories of Language acquisition to establish the relevance of drama-in-education to the domain of teaching and learning and probably language teaching. It further x-rays the mimesis concept of drama as a basis and model for language learning by explaining the three imitative models of language learning among humans as they relates to communicative activities: to prove the relevance of drama as a potent tool for fostering effective communication skills in English as Second Language Learners.